PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, KECERDASAN INTELEKTUAL DAN INDEPENDENSI PADA KINERJA AUDITOR - Yuliana, Grece Setiawan; Latrini, Made Yenni (E-Jurnal Akuntansi, 2016)
This study aims to determine the effect of emotional intelligence, spiritual intelligence, intellectual intelligence, and independence on the perfomances of the auditors at KAP in Bali. The samples were selected using technique non probability sampling with purposive sampling of sample obtained as many as 50 sample. The data was obtained through the deployment of a questionnaire to the auditors. The analytical technique the data used regression analysis linear multiple. Based on the results, it is known that the emotional intelligence, spiritual intelligence, intellectual intelligence, and independence give a positive impact of the performances of the auditors. This showed that the increase emotional intelligence, spiritual intelligence, intellectual intelligence, and independence of then performance auditor the increased as well.
Keywords: performance of auditor, emotional intelligence, spiritual intelligence, intellectual intelligence, independence